Incorporation with the Implementation of Verbs in Aceh - Wahyu Maulana; Mulyadi (Britain International for Academic Research (BIAR) Publisher, 2022)
Incorporation is a morphological linguistic phenomenon. Incorporation itself is usually defined simply by using the definition of 'word combination'. The purpose of this study is to analyze the phenomenon of incorporation of verb disappearance in the Acehnese language. This research is expected to contribute to the development of Acehnese language science. The source of the data used is taken from coil.com which provides news in Acehnese language. From the data that has been collected, the researchers found that there are at least three types of incorporation of verb incorporation in the Acehnese language; objective incorporation, locative incorporation, and state incorporation. In his analysis, the researcher found that the affixation of 'geu-' and 'meu' had a role in the formation of verb incorporation in the Acehnese language.